Gênero e poder nas obras de Artemisia Gentilesch - Santos, Fernanda Nascimento dos (2021)
This article aims to analyze the works “Judite beheading Holofernes” and “Judite and the maidservant” by the painter Artemisia Gentileschi, between 1613 and 1621, an artist who lived in the historical context of the Italian peninsula between the 16th and 17th centuries. Through her artistic career, she had her legacy perpetuated in the representation of gender, perpetuating herself in the world's pictorial culture. The recent 20th century rediscovery of Artemisia revealed how her works established a new perspective on the Renaissance concept of art, in which the women represented by the author of the works are heroic and not sexually manipulated, going against a concept originating in Europe